Technologies implemented in the business environment: Smart pillar for enhancing organisational performance - Alina Suslenco; Marilena Doncean; Octavian Cozniuc (CES Working Papers, 2023)
This paper takes us on a methodological journey, analysing the efficiency of implementing information technologies in the business environment. In the context of digital transformation of the SMEs in the EU, Romania, and the Republic of Moldova emerges the necessity to focus on implementing information technologies in the business area, as the primary factor of boosting organisational performance. The aim of this research is to shed light on the possibilities of implementing information technologies in the business environment of Romania and the Republic of Moldova. The methodology of this scientific endeavour has been geared towards using multiple methods of research, among which stands out the quantitative research, the inquiry used as a research tool, namely a questionnaire. The results of the research show a direct interconnection between implementing information technologies and customer satisfaction, particularly organisational performance. Thus, organisations aspiring to grow their performance should remodel their management system in terms of implementing new information technologies which will increase customer trust, improve client satisfaction, and gain customer loyalty to the products/ services provided by the company concerned.
Keywords: 330; information technologies; relationship management; organisational performance; SMART pillar